Effects of a commercial antibiotic and a microbial preparation on the productive performance and pigs health during fattening - Flores, Luis; Elías, Arabel; Proaño, F.; Granizo, G.; Medina, Yolaine; López, Sandra; Herrera, F.; Caicedo, William (Cuban Journal of Agricultural Science, 2016)
To measure the influence of a Stafac (Virginiamicina at 2%, 1 kg.t-1) commercial antibiotic regarding to a microbial preparation in the productive performance and diarrheas occurrence during pig fattening, an experiment by a completely randomized design was conducted, with three treatments and four repetitions: T1) concentrate, T2) concentrate + commercial antibiotic,T3) concentrate + microbial preparation. A total of 120 barrow males were used, from Landrace x Large White cross, with Belga x Pietrain White sire, of 71 d of age, 28.62kg average weight ± 2.66 kg. It was determined that, for final weight, with the concentrate plus the microbial preparation 98.41 kg of LW was obtained. This value was higher to that of the concentrate plus antibiotic and to the concentrate. For the daily weight gain and final weight gain, the best values corresponded to the concentrate plus microbial preparation, with 712.6 g and 69.84 kg respectively, which were above of the obtained for the concentrate plus antibiotic and the concentrate. In food conversion there were not significant differences between treatments. The group of animals fed with concentrate plus microbial preparation had lower number of diarrheas, with 9.25 of incidence. With the addition of this microbial preparation, better productive parameters and of health in pig fattening can be obtained, without using antibiotics.Key words: microbial preparation, commercial antibiotic, fattening pig, whey